Efektivitas Penggunaan Media Wordwall terhadap Hasil Belajar IPAS Materi Gaya SD Negeri 1 Tahunan - Salsabiela Berliana; Aan Widiyono (Universitas Ngudi Waluyo, 2025)
Abstract The purpoose of this study was to evaluate the impact of Wordwall media on science learning outcomes (IPAS) for the topic